The United Kingdom and the European community Alan S. Milward. - Milward, Alan S. (Alan Steele), 1935- (Government official history series, 2002)
This text analyses British official thinking behind the UK's standing aloof from the moves after 1945 towards European economic collaboration. The volume ends with General de Gaulle's veto of 1963.